Construction of Cu(ii), Zn(ii) and Cd(ii) metal–organic frameworks of bis(1, 2, 4-triazol-4-yl)ethane and benzenetricarboxylate: syntheses, structures and photocatalytic properties1. Issue 12 (28th March 2015) - Peng, Yan-Fen; Zhao, Shan; Li, Ke; Liu, Lu; Li, Bao-Long; Wu, Bing
<x xml:space="preserve">Abstract</x> Three coordination polymers based on 1, 2-bis(1, 2, 4-triazol-4-yl)ethane and 1, 2, 3-benzenetricarboxylate were synthesized and characterized. 1 and 2 show good photocatalytic activity for the degradation of methyl orange.